Opportunities for ecotourism development with complementary cultural heritage: The case study of ?a?alica Memorial Park - Aleksandar Antić (Mенаџмент у хотелијерству и туризму, 2017)
Modern trends in tourism worldwide are pointing out the rural aspect of tourism business, and the return of tourists to nature as a retreat from daily stressful life in cities. The form of tourism which clearly creates the setting for such a development is ecotourism. The most important aspects of ecotourism are conservation, education and relaxation. To function properly in a local community, ecotourism needs an adequate commitment of tourism employees and the local population. The research is based on the general hypothesis that there are opportunities for the development of ecotourism in Požarevac. The research empoyed case study with SWOT analysis undertaken for ?a?alica Memorial Park. The interview with staff in the Tourist Organization of Požarevac helped in preparing the SWOT analysis of the observed ecological site.